Market Development for Genetically Modified Foods 2001
DOI: 10.1079/9780851995731.0007
|View full text |Cite
|
Sign up to set email alerts
|

A way forward for Frankenstein foods.

Abstract: This chapter reports the findings from some preliminary analyses of the impact on prices at farm gate and at retail of introducing a system of retail labelling of non-genetically modified food. Of interest here is the nature of market segmentation and price differentiation after a first generation genetically modified (GM) crop (rape, in this example) is produced and marketed. The simple model presented explores some possible scenarios for future prices for GM and non-GM rape under a few key assumptions. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Some earlier studies have assumed GM adoption requires the introduction of SIP systems, and have suggested their cost could amount to as much as 15 per cent of the farm-gate price of the GM product (e.g., Burton et al 2002). These costs would be spread along the value chain (see details in Bullock and Desquilbet 2002) and so shared between producers and consumers, including for non-GM varieties; and the fixed cost of their introduction would be amortised.…”
Section: Productionmentioning
confidence: 98%
“…Some earlier studies have assumed GM adoption requires the introduction of SIP systems, and have suggested their cost could amount to as much as 15 per cent of the farm-gate price of the GM product (e.g., Burton et al 2002). These costs would be spread along the value chain (see details in Bullock and Desquilbet 2002) and so shared between producers and consumers, including for non-GM varieties; and the fixed cost of their introduction would be amortised.…”
Section: Productionmentioning
confidence: 98%
“…We did that implicitly by choosing conservative cost savings due to the new technology, saying they were net of any fees charged for segregation and identity preservation. According to Burton et al (2002) such fees may be as high as 15% of farm gate price, which would make it unprofitable to market many GM varieties if that was a required condition of sale. Others suggest those costs could be miniscule-at least in developed economies-on the grounds that such segregation is increasingly being demanded by consumers of many conventional foods anyway (e.g., different grades or varieties or attributes of each crop) so the marginal cost of expanding such systems to handle GMness would not be great, at least in countries that have already shown a willingness to pay for product differentiation.…”
Section: Caveatsmentioning
confidence: 99%
“…We did that implicitly by choosing conservative cost savings due to the new technology, saying they were net of any fees charged for segregation and identity preservation. According to Burton et al (2002) such fees may be as high as 15 % of farm gate price, which would make it unprofitable to market many GM varieties if that was a required condition of sale. Others suggest those costs could be miniscule on the grounds that such segregation is increasingly being demanded by consumers of many conventional foods anyway (e.g., different grades or varieties of each crop) so the marginal cost of expanding such systems to handle GM-ness would not be great, at least in countries willing to pay for product differentiation.…”
mentioning
confidence: 99%